CHRISTIAN CENTRE DI GORONTALO - Desi Yuliyana Manggombo; Lydia Tatura; Kalih Trumansyahjaya (JAMBURA Journal of Architecture, 2021)
ABSTRACT The main Objective Of designing the Christian Center in Gorontalo is to fulfill the religious needs of a religion, namely Protestan Christianity, with the hope of achieving the desire of the Christian community in Gorontalo to be more active in spiritual activities which will certainly promote the city of Gorontalo it self, making superior seeds. Servants as well as creating, orogonated in this city. Theapplication of symbolic architecture is expressed in the physical form of designs such as zoning, circulation and buildings. The physical form of the design is used as a communication medium of Christian symbols and philosophies that are applied in the design. The result of this design is the design of Christian Areas in Gorontalo City, especially the GPIG Synod Region 1. Keywords : Christian Center in Gorontalo, Symbolic Architecture ABSTRAK Tujuan utama perancangan Christian Centre Di Gorontalo ini adalah untuk memenuhi kebutuhan religi suatu agama yaitu Krsiten Protestan, dengan harapan tercapainya keinginan masyarakat kristen di gorontalo untuk lebih aktif lagi dalam beribadah dan kegiatan kerohanian yang nantinya tentu dapat memajukan kota gorontalo ini sendiri, menciptakan bibit-bibit unggul pelayan dan juga generasi, berawal dari kota ini. Penerapan Arsitektur Simbolik dituangkan dalam bentuk fisik perancangan seperti penzoningan, lansekap, sirkulasi dan bangunan. Bentuk fisik perancangan digunakan sebagai media komunikasi dari simbol dan filosopi Kristen yang diterapkan dalam perancangan. Hasil rancangan ini berupa perancangan Kawasan Kristen di Kota Gorontalo Khususnya Sinode GPIG Wilayah 1. Kata Kunci : Christian Centre Di Gorontalo, Arsitektur Simbolik